THE MULTIDIMENSIONAL-PROGRESSIVE LOGIC OF AL-MAQASID AL-SYARI’AH FOR THE DEVELOPMENT OF HUMANITARIAN FIQH - Shofi, Muhammad Aminuddin; Bayhaki, Imam; Hesan, Mochammad (Balai Penelitian dan Pengembangan Agama Makassar, 2023)
This research aims to describe Jamaluddin Athiyyah’s thought both conceptually and in operational logic, as well as the factors of human values in al-maqa>sid al-syariah and its progressive legal reasoning. This research is a literature with primary legal materials, books by Athiyyah, and various latest scientific journals. Research findings show that conceptually according to Athiyyah, the benefits that are the objectives of Sharia are universal and balanced, the urgency of understanding must be balanced between and the method of ushul Fiqh and Fiqh rules, so that the legal product is not textual-conservative or liberal subjective. According to Athiyyah, the factors of human values in al-maqasid al-syariah are:1) Efforts to get to know, help, and complement each other, 2) Realization of the role of the human caliph on earth, 3) Realization of peace based on the value of justice, 4) State protection of human rights, and 5) Spread of Islamic da'wah. reasoning focuses on the substance of the goal to be achieved (ideal norms) in the enactment of a law. It is not just legal-formal legitimacy or legal rules labeled Sharia. Such legal logic is more progressive and elastic substantively and more politically dynamic to respond to the dialectic of Sharia and law in the development of national law. This research is expected to contribute to theprogressive implementation of al-maqa>sid al-syari>ah in the context of developing humanist and universal Islamic law.